2020
DOI: 10.1108/jabs-02-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting consumers' pro-environmental behaviour in nutricosmetics consumption: the role of perceived environmental responsibility as a mediator

Abstract: Purpose This study aims to examine the direct effect of compensatory health beliefs (CHBs), environmental self-identity and perceived environmental responsibility (PER) towards consumers' pro-environmental behaviour (PEB). Moreover, this study also investigates the mediating role of PER. Design/methodology/approach Data were collected from nutricosmetics consumers in Malaysia. A questionnaire survey was carried out in three major shopping complexes in Klang Valley areas, which generated 448 completed usable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 84 publications
(94 reference statements)
0
5
0
1
Order By: Relevance
“…A few research studies have demonstrated that environmental responsibility has been considered a mediating variable to explain consumers' pro-environmental behaviors. Shahrin et al [61] examined the mediating role of environmental responsibility between "compensatory health beliefs and pro-environmental behavior" and "environmental self-identity and pro-environmental behavior" in nutricosmetics consumption.…”
Section: Hypothesis 2c (H2c)mentioning
confidence: 99%
“…A few research studies have demonstrated that environmental responsibility has been considered a mediating variable to explain consumers' pro-environmental behaviors. Shahrin et al [61] examined the mediating role of environmental responsibility between "compensatory health beliefs and pro-environmental behavior" and "environmental self-identity and pro-environmental behavior" in nutricosmetics consumption.…”
Section: Hypothesis 2c (H2c)mentioning
confidence: 99%
“…This further enriches the theory related to eco-purchasing behavior. The positive effects of consumer ecological responsibility [28][29][30][31][89][90][91] and ecological attitude [14,19,[22][23][24] on ecological purchasing behavior were verified. Environmental concern, as a psychological cognitive factor, had positive effects on consumers' ecological attitudes.…”
Section: Theoretical Implicationsmentioning
confidence: 86%
“…Follows and Jobber, on the other hand, proposed the value-attitude-intention-behavior mechanism to explore ecological purchasing behavior, where the type of value is an important factor in forming different consumer attitudes, as well as an ex-factor that ultimately promotes ecological responsibility and purchasing [30]. Shahrin et al then verified that environmental responsibility can influence ecological purchasing behavior based on social cognitive theory [31]. Therefore, consumers' ecological responsibility is positively associated with ecological purchasing intentions.…”
Section: Ecological Responsibility and Ecological Purchasing Behaviormentioning
confidence: 99%
“…There is also a growing interest in research on consumers’ pro-environmental behavior in developing and emerging economies, as researchers have suggested that some global problems, such as plastic pollution, stem predominantly from developing countries (Chaudhary et al , 2021). Recent pro-environmental research examined work in Indonesia (Tamar et al , 2020), Malaysia (Shahrin et al , 2020), India (Mohanty et al , 2021) and Ghana (Amoah and Addoah, 2021), to name only a few. These countries are equally important in the achievement of the 2030 goals, with some questioning whether developing countries will achieve these targets (Asadullah et al , 2020).…”
Section: Methodsmentioning
confidence: 99%